Desinserción de los músculos depresor del septum y orbicular de los labios de la premáxila como tratamiento coadyuvante en rinoplastia para mejorar la rotación de la punta nasal: experiencia en 45 pacientes - Sarmiento A., Diego; Kuroiwa R., Maya (Revista Hospital Clínico Universidad de Chile, 2011)
The nose muscles have a rudimentary action in humans with the exception of dilator naris muscle and depressor septi nasi muscle. The depressor septi nasi muscle has an important role pulling the nasal tip caudally while smiling, along with the orbicularis oris muscle. The detachment of this muscle from the premaxilla produces a dynamic rhinoplasty of the nasal tip. The objective of this study is to determine the importance of the detachment of the depressor septi nasi muscle and orbicularis oris muscle from the premaxillar bone in rhinoplasties of patients with a drooping nasal tip while smiling. 45 patients that underwent dynamic rhinoplasty were analized. All patients had an excellent postoperative evolution, with improvement of the drooping tip; this was demonstrated by direct nasolabial angle measuring and by photographic analysis. The detachment of the depressor septi nasi muscle and orbicularis oris muscle is a simple and reproducible technique, with limited morbidity and used during rhinoplasty that enhances the nasal tip rotation.